2020
DOI: 10.35940/ijrte.e5906.018520
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Interest Rates on Private Saving with Reference to Myanmar

Abstract: The private saving is one of the fundamentals for economic development and growth of the country. Thus, the main purpose of this paper is to analyze the effect of interest rates on private saving in Myanmar over the period from fiscal year 2013-14 Q1 to 2018 Q2. This study investigates the private saving of Myanmar’s banking sector which includes twenty seven private commercial banks, four State-owned banks and thirteen foreign bank branches. The quarterly data are obtained from secondary data sources collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Using a multiple regression analysis and correlation tools, their results divulged that all independent variables have a significant impact on savings but the Treasury bill did not have a significant impact. Their results also revealed that the saving deposit rate is the most influential variable in attracting private savings (Tun et al, 2020).…”
Section: Mckinnonmentioning
confidence: 95%
See 1 more Smart Citation
“…Using a multiple regression analysis and correlation tools, their results divulged that all independent variables have a significant impact on savings but the Treasury bill did not have a significant impact. Their results also revealed that the saving deposit rate is the most influential variable in attracting private savings (Tun et al, 2020).…”
Section: Mckinnonmentioning
confidence: 95%
“…The result of the OLS shows that interest rate spread and exchange rate, inflation, savings, interest, and GDP growth rate are statistically insignificant in their effect on savings (Brotoboh, Obeh, 2021). Tun, Mohamed, Alrajawy and Bhaumik (2020) studied the influence of interest rates on private saving in Myanmar between 2013-2014 Q1 and 2018 Q2. Using a multiple regression analysis and correlation tools, their results divulged that all independent variables have a significant impact on savings but the Treasury bill did not have a significant impact.…”
Section: Mckinnonmentioning
confidence: 99%